Ontologi Islam dan Konsep Nilai dalam Ekonomi: Mewujudkan Keadilan dan Kesejahteraan Melalui Perspektif Spiritual - Fajri Romadhoni; Maryam Batubara (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This paper discusses Islamic ontology and the concept of value in an economic context, with a focus on the perspective of purpose and meaning of life. Islamic ontology refers to the Islamic view of reality and existence, which includes an understanding of the relationship between humans, the universe, and God. This paper explores how Islamic ontology influences the concept of value in economics. This article presents a framework for Islamic ontological thought, including views on the purpose and meaning of life from a religious perspective. This paper concludes that Islamic ontology provides a strong foundation for the concept of value in economics. In this context, the purpose and meaning of life is seen as more than just achieving material success, but also involves spiritual achievement and sustainable happiness. By considering the purpose and meaning of life in an economic context, we can direct our economic efforts to achieve more meaningful and sustainable success, which includes both material and spiritual aspects of human life.